Uridine diphosphate glucuronosyl transferase 1A (UGT1A1) promoter polymorphism in young patients with sickle cell anaemia: report of the first cohort study from Nigeria - Oladele Simeon Olatunya; Dulcineia Martins Albuquerque; Ganiyu Olusola Akanbi; Olufunso Simisola Aduayi; Adekunle Bamidele Taiwo; Opeyemi Ayodeji Faboya; Tolorunju Segun Kayode; Daniela Pinheiro Leonardo; Adekunle Adekile; Fernando Ferreira Costa (BMC, 2019)
Abstract Background (TA) n repeat sequence (rs8175347) of UGT1A1 gene promoter polymorphism is associated with serum bilirubin levels and gallstones among different sickle cell anaemia (SCA) populations. There are no data on UGT1A1 polymorphisms and their impact on Nigerian SCA patients. In this study, we determined the distribution of the UGT1A1 (TA) n genotypes among a group of young Nigerian SCA patients and healthy controls. In addition, the influence of UGT1A1 (TA) n genotypes on the laboratory and clinical events among the patients was determined. Methods The distribution of the UGT1A1 (TA) n genotypes among 101 young Nigerian SCA patients and 64 normal appropriate controls were determined and studied. The UGT1A1 (TA) n genotypes were further classified into subgroups and used to differentiate the clinical events and laboratory parameters of the patients. Results Four (TA) n alleles:(TA)5, 6, 7, and 8 were found. These were associated with 10 genotypes: TA5/5, 5/6, 5/7, 5/8, 6/6, 6/7, 6/8, 7/7, 7/8, 8/8. The normal (wild-type)-(TA) 6/6), low- (TA) 7/7, 7/8, 8/8), intermediate- (TA) 5/7, 5/8, 6/7, 6/8), and high-activity (TA) 5/5, 5/6,) genotypes were found in 24.8, 24.8, 41.5, and 8.9% patients and 20.3, 15.6, 61, and 3.1% controls respectively. The general genotype distribution of the patients and control group were not significantly different. There were significant differences in serum bilirubin and lactate dehydrogenase (LDH) of the patients when differentiated by the UGT1A1 (TA) n genotypes (p<0.05). Asymptomatic gallstones were found in 5.9% of patients and were significantly of the low-activity genotypes sub-group 5 (20%) vs 1(1.3%) p = 0.0033. Although, bilirubin and fetal hemoglobin (HbF) of patients with gallstones were significantly different from those without gallstone, only the serum bilirubin was associated with UGT1A1 (TA) n genotypes on multivariate analysis (p < 0.0001). Conclusion This study highlights the contribution of UGT1A1 polymorphisms, a non-globin genetic factor, to the laboratory and clinical manifestations of young Nigerian SCA patients for the first time. It also shows that children with co-inheritance of low UGT1A1 (TA) n affinity genotypes may be at risk of gallstone, hence the need to follow them up.